O conhecimento sobre a ecologia e biodiversidade de aves por alunos do ensino fundamental - Soares, Talita Pereira (Universidade Federal de São Carlos, 2021)
The human impact are increasingly intense worldwide, demanding a new attitude from society in relation to the environment. In Brazil, a relationship of greater concern with environmental issues has been growing over the last years. Thus, the importance of having environmental education teaching in scholar curriculum increases in order to create critical and reflective citizens capable of finding a way to reduce the human impact on the environment. This is the objective of Environmental Education in schools, but this theme is still underdeveloped, with a great distance between people and the reality on the ground. Likewise, the popular knowledge of students is little explored in general themes when it comes to the subject of ecology and biology of birds. The objective of this study was to address the knowledge of bird ecology and biology in the seventh year of the elementary school in a state public school in São Carlos, São Paulo state, Brazil. I applied a questionnaire containing subjective and objective questions evidencing the knowledge of the birds of each student. When analyzing the obtained responses, I found that the students had a reasonable knowledge on bird names. Analyzing the answers on bird species identification based on their pictures, in relation to the species cited by them, I noticed that many students could not identify the species cited in the previous question. However, when assessing the questions on the characteristics on the species and their biology, I realized the poor knowledge of the students, which did not corroborate the responses to the questions on identification and citation of species names. This study suggest that better results can reach if the students have an approximation to the ecological and biological concepts that involve their popular knowledge about birds, embracing other curricular topics. In this way, we can build a way in which this generation has a greater understanding of the anthropic impacts that have been happening over thousands of years and how they can change this scenario.
Knowledge about the ecology and biodiversity of birds by elementary school students
Keywords: Educação ambiental; Etnoornitologia; Questionário; Environmental education; Ethno-ornithology; Questionnaire; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM